2012
DOI: 10.5194/bg-9-4773-2012
|View full text |Cite
|
Sign up to set email alerts
|

Landscape control of uranium and thorium in boreal streams – spatiotemporal variability and the role of wetlands

Abstract: The concentrations of uranium and thorium in ten partly nested streams in the boreal forest region were monitored over a two-year period. The investigated catchments ranged from small headwaters (0.1 km<sup>2</sup>) up to a fourth-order stream (67 km<sup>2</sup>). Considerable spatiotemporal variations were observed, with little or no correlation between streams. The fluxes of both uranium and thorium varied substantially between the subcatchments, ranging from 1.7 to 30 g km<sup>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The area is up to 94% dominated by metagreywacke, which is overlain by mainly till in the upper parts of the catchment and glaciofluvial silt and sand deposits in the lower parts (Supporting Information, Figure S1). Both airborne gamma spectrometry 13 and analyses of soil cores and soil water throughout the catchment 33 indicate that the chemical composition of the mineral soils is homogeneous. The entire Krycklan catchment covers 68 km 2 , but within the framework of the Krycklan Catchment Study (KCS) 15 subcatchments are regularly sampled and analyzed for a wide range of hydrochemical parameters.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
See 2 more Smart Citations
“…The area is up to 94% dominated by metagreywacke, which is overlain by mainly till in the upper parts of the catchment and glaciofluvial silt and sand deposits in the lower parts (Supporting Information, Figure S1). Both airborne gamma spectrometry 13 and analyses of soil cores and soil water throughout the catchment 33 indicate that the chemical composition of the mineral soils is homogeneous. The entire Krycklan catchment covers 68 km 2 , but within the framework of the Krycklan Catchment Study (KCS) 15 subcatchments are regularly sampled and analyzed for a wide range of hydrochemical parameters.…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…dissolved organic carbon (DOC) and elements such as Fe, Al, P, Mn, and Se. 6−12 Recently, Lidman et al 13 demonstrated that the fluxes of U and Th in small boreal streams are strongly influenced by wetlands, suggesting that wetlands may reduce the transport of U and Th from the boreal forest landscape by as much as 30− 40%. Investigations of a wetland in the same area also confirmed that the these numbers are consistent with the amounts of U and Th that historically have been accumulated in the peat.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…4). As concerns the stream, in turn, it is known from previous research that it is, in many respects, typical for forested catchments in the area (Cory et al, 2006;Björkvald et al, 2008;Lidman et al, 2012Lidman et al, , 2014Köhler et al, 2014). Despite their size, small streams and headwaters are important for generating runoff in the boreal landscape, even in large rivers (Bishop et al, 2008).…”
Section: The Role Of Riparian Soils In the Boreal Landscapementioning
confidence: 99%
“…Some studies estimating the spatial variability of trace elements in Scandinavia, at spatial scales from 10-100 km 2 , have been published (Tarvainen et al, 1997;Edén et al, 1999;Andersson et al, 2006;Dahlqvist et al, 2007;Reimann et al, 2009;Lidman et al, 2012). The novel focus in this study is on headwaters, < 2 km 2 , in combination with larger streams in the channel network of complete rivers, including the lakes embedded in those networks.…”
Section: Introductionmentioning
confidence: 99%